2020
DOI: 10.1161/circulationaha.120.045810
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Evaluation of the Comorbidity-Inflammation Paradigm in Heart Failure With Preserved Ejection Fraction

Abstract: Background: A systemic pro-inflammatory state has been hypothesized to mediate the association between comorbidities and abnormal cardiac structure/function in heart failure with preserved ejection fraction (HFpEF). We conducted a proteomic analysis to investigate this paradigm. Methods: In 228 HFpEF patients from the multicenter PROMIS-HFpEF study, 248 unique circulating proteins were quantified by a multiplex immunoassay (Olink) and used to recapitula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 50 publications
10
150
0
Order By: Relevance
“…Apart from their role in HF, IL-1β and IL-6 are key pro-inflammatory factors in many diseases, like COPD ( 186 ), diabetes ( 187 ), kidney disease ( 188 ), sarcopenia, obesity, and HF ( 189 ), and the cytokine storm in COVID-19 ( 190 ). A recent study on HFpEF supported that systemic inflammation may be the association between comorbidity and HF ( 191 ). The IL-1β and IL-18 signaling pathways may be novel drug targets for HFpEF, which are important in the mitochondria-inflammation circuit ( 192 ).…”
Section: Link Between Heart Failure and Comorbiditiesmentioning
confidence: 99%
“…Apart from their role in HF, IL-1β and IL-6 are key pro-inflammatory factors in many diseases, like COPD ( 186 ), diabetes ( 187 ), kidney disease ( 188 ), sarcopenia, obesity, and HF ( 189 ), and the cytokine storm in COVID-19 ( 190 ). A recent study on HFpEF supported that systemic inflammation may be the association between comorbidity and HF ( 191 ). The IL-1β and IL-18 signaling pathways may be novel drug targets for HFpEF, which are important in the mitochondria-inflammation circuit ( 192 ).…”
Section: Link Between Heart Failure and Comorbiditiesmentioning
confidence: 99%
“…These factors, combined with a lack of robust animal models, has hindered the development of new treatments [ 36 ]. It is apparent from both human and murine studies that there is a link between comorbidities associated with systemic inflammation and the development of HFpEF [ 37 , 38 , 39 ], and that inflammation-related biomarkers are strongly associated with HFpEF severity and outcome [ 40 ].…”
Section: Inflammation: the Link Between Ra And Cvdmentioning
confidence: 99%
“…Inflammation undoubtedly plays a role in both forms of HF albeit via different mechanisms. HFpEF is associated with higher levels of circulating biomarkers of inflammation than HFrEF, which is associated with higher levels of markers of myocyte stress and progressive loss of cardiomyocytes [ 38 , 60 , 61 ]. Systemic inflammation results in increased levels of circulating pro-inflammatory cytokines such as TNF-alpha and interleukin-6, leading to endothelial activation, nitrosative and oxidative stress, increased myocardial stiffness, and fibrosis, ultimately resulting in diastolic dysfunction as a result of impaired relaxation of the myocardium [ 60 ].…”
Section: The Role Of Inflammation In Heart Failurementioning
confidence: 99%
“…Inflammation is widely recognized to play a crucial role in the pathogenesis of both HF with reduced and preserved ejection fraction. Systemic inflammation is frequently associated with abnormal cardiac structure and function in clinical studies ( Suzuki et al, 2008 ; Sanders-van Wijk et al, 2020 ): nevertheless, conflicting outcomes have also been documented. In the Canakinumab Anti-Inflammatory Thrombosis Outcomes Study (CANTOS) ( Ridker et al, 2012 ), anti-interleukin (IL)-1β treatment demonstrated a reduction in inflammatory markers in type 2 DM (T2DM); however, over a longer duration, it failed to reduce the risk of cardiovascular events ( Tan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%